Editorial Introduction: Unveiling new dimensions in policy process theory research. - Song, Geoboo; Siddiki, Saba; Merry, Melissa K.; Mondom, Davor; Galloway, Ben; Arnold, Gwen; Smith‐Walter, Aaron; Peterson, Holly L.; Tumlison, Creed; Huett, Briana; Choi, Heasun; Borozdina, Nataliia (Policy Studies Journal, 2024)
The Policy Studies Journal's third issue for 2024 features 10 articles that explore various aspects of policy process theories and substantive policy domains. The journal has experienced a significant increase in submissions, indicating its growing prominence and interest in policy studies. The editorial team has made progress in managing the increased volume of submissions and has introduced new publication formats, such as Perspectives and Research Notes, to address emerging research topics. The journal has also engaged in collaborations and initiatives to foster communication and exchange within the policy community. The current issue includes articles on topics such as issue attention in policy research, the decline of incrementalism in US lawmaking, and the impact of anxiety on policy learning. Overall, the journal aims to provide valuable insights into policymaking processes and outcomes across diverse contexts.